In vitro toxicity screening of silica-coated superparamagnetic iron oxide nanoparticles in glial cells - Costa, Carla (2016)
Nanotechnology industry is progressing with prospects of substantial benefits to economics and science. Superparamagnetic iron oxide nanoparticles (ION) have been showing excellent magnetic properties, biocompatibility and biodegradability, broadening their potential applications and importance in the biomedical field